Pengaruh leverage, intensitas modal, dan intensitas persediaan terhadap tarif pajak efektif pada perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia Tahun 2019-2022 - Cheristine Monica; Kezia Josephine (LPMP Imperium, 2024)
This research study investigates the effective tax rates. It aims to provide empirical evidence of the impact of leverage, capital, and inventory intensity on the effective tax rate. The study uses specific selection criteria to focus on manufacturing companies listed on the Indonesia Stock Exchange from 2019 to 2022. A total of sixty-eight companies were chosen as samples through purposive sampling. The samples were then analyzed and tested using the multiple linear regression method. The study results indicate that the leverage variable affects the effective tax rate. At the same time, capital intensity does not affect the effective tax rate. On the other hand, inventory intensity has also been proven to affect the company's effective tax rate. Public interest statements Investors should consider various financial ratios to maximize profits. This study's findings can provide guidance for making informed decisions. Companies should prioritize factors that attract investor interest and ensure accurate completion of financial reports. The study's results can help them better understand these factors. Future researchers should consider adjusting variables to improve the effectiveness of the tax rate. The study's findings can serve as a starting point for their research.